(untitled) (Al-Qamar, 2023)
The aim of this research study was to investigate the Leadership Practices, School Environment and Academic Achievement at Secondary Schools in Nasirabad division, Balochistan province. The study was also aimed at exploring the effect of head teachers` Leadership Practices on Academic Achievement and School Environment at Secondary Schools. The related literature was reviewed which dealt with different aspects of leadership practices along with school environment which suits to run the school matters better of learning and teaching environment which eventually lead to improve academic achievement of students. Methodology: The descriptive survey design with quantitative approach was used to conduct this study. A descriptive survey approach is more appropriate for collecting a huge data from the large number of sample at one point in time (Babbie, 2007; Cresswell, 2008). Likert Scale Questionnaire 0.5 was used to collect the response from participants. Data Analysis: Statistical analysis technique was used to analyze the data via SPSS statistical software Findings: The findings of the regression analysis revealed that there is a positive impact of leadership practices on school environment. It was also revealed by the statistical analysis that the better leadership practices can bring about a prominent change in students` academic achievement.